2020
DOI: 10.5194/acp-2020-398
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impacts of coagulation on the appearance time method for sub-3 nm particle growth rate evaluation and their corrections

Abstract: <p><strong>Abstract.</strong> The growth rate of atmospheric new particles is a key parameter that determines their survival probability to become cloud condensation nuclei and hence their impact on the climate. There have been several methods to estimate the new particle growth rate. However, due to the impact of coagulation and measurement uncertainties, it is still challenging to estimate the initial growth rate of sub-3 nm particles, especially in pol… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…For instance, the observed GR in the sub-3 nm size range is influenced by the estimation method and, thus, has an impact on the ratios of the calculated GR 1−3 over the observed GR 1−3 . As shown in Figure S6b, a recently corrected appearance time method 21 gave higher values of the observed GR 1−3 than the log-normal distribution function method and, thus, lower ratios. Nevertheless, results from both methods support that the condensation of H 2 SO 4 and its clusters contributes significantly to the growth of particles in the sub-3 nm size range.…”
Section: Methodsmentioning
confidence: 87%
See 1 more Smart Citation
“…For instance, the observed GR in the sub-3 nm size range is influenced by the estimation method and, thus, has an impact on the ratios of the calculated GR 1−3 over the observed GR 1−3 . As shown in Figure S6b, a recently corrected appearance time method 21 gave higher values of the observed GR 1−3 than the log-normal distribution function method and, thus, lower ratios. Nevertheless, results from both methods support that the condensation of H 2 SO 4 and its clusters contributes significantly to the growth of particles in the sub-3 nm size range.…”
Section: Methodsmentioning
confidence: 87%
“…Also, due to the underestimation of the coagulation effect, new particle formation rates from the Cosmics Leaving OUtdoor Droplets (CLOUD) chamber studies on sulfuric acid-dimethylamine nucleation were later corrected to be a factor of 10 faster than previously published results. 20 In addition, Cai et al 21 showed that neglecting coagulation scavenging can result in overestimation when evaluating the particle growth rate from the measured data.…”
Section: Introductionmentioning
confidence: 99%
“…The measured data for Fig. 8 are available at https://doi.org/10.5281/zenodo.4506345 (Cai, 2021). The simulation results shown in Figs.…”
mentioning
confidence: 99%